Fault2SeisGAN: A method for the expansion of fault datasets based on generative adversarial networks - Zhao, Shuo; Ding, Renwei; Han, Tianjiao; Liu, YiLin; Zhang, Jinwei; Zhao, Lihong (Frontiers in Earth Science, 2023)
The development of supervised deep learning technology in seismology and related fields has been restricted due to the lack of training sets. A large amount of unlabeled data is recorded in seismic exploration, and their application to network training is difficult. To solve this problem, herein, we propose an end-to-end training data set generative adversarial network (GAN), Fault2SeisGAN. This network can expand limited labeled datasets to improve the performance of other neural networks. In the proposed method, the Seis-Loss is used to constrain horizon and amplitude information, Fault-Loss is used to constrain fault location information, and the Wasserstein distance is added to stabilize the network training to generate seismic amplitude data with fault location labels. A new fault identification network model was trained with a combination of expansion and original data, and the model was tested using actual seismic data. The results show that the use of the expanded dataset generated in this study improves the performance of the deep neural network with respect to seismic data prediction. Our method solves the shortage of training data set problem caused by the application of deep learning technology in seismology to a certain extent, improves the performance of neural networks, and promotes the development of deep learning technology in seismology.